413. Association of SARS-CoV-2 Genomic Load in Nasopharyngeal Samples with Adverse COVID-19 Patient Outcomes: A Retrospective Analysis from an Academic Hospital Center in New York City. (31st December 2020) - Zacharioudakis, Ioannis; Prasad, Prithiv; Zervou, Fainareti; Basu, Atreyee; Inglima, Kenneth; Weisenberg, Scott; Aguero-Rosenfeld, Maria E
Abstract: Background: SARS-CoV-2, the cause of COVID-19 pneumonia, is associated with heterogenous presentations ranging from asymptomatic infection to severe respiratory failure. We explored the association of SARS-CoV-2 genomic load as a risk factor for adverse patient outcomes. Methods: We included adult patients admitted to the hospital with clinical and radiographic findings of pneumonia and a confirmatory polymerase chain reaction (PCR) test of SARS-CoV-2 within 24 hours of admission. We segregated patients into 3 genomic load status groups: low (Cycle threshold (Ct) ≥35) intermediate (25< Ct< 35) and high (Ct ≤25) using real-time PCR. The primary outcome was a composite outcome of death, intubation and/or use of extracorporeal membrane oxygenation. Secondary outcomes included severity of pneumonia on admission, as measured by the Pneumonia Severity Index (PSI). Sensitivity analyses were performed to include Acute Respiratory Distress Syndrome (ARDS) in the composite outcome and varying Ct classification breakpoints. Results: Of 457 patients positive for SARS-CoV-2 assay from March 31 st to April 10 th 2020, 316 met inclusion criteria and were included in the final analysis. Included patients were followed for a median of 25 days (IQR 21–28). High genomic load at presentation was associated with higher Charlson Comorbidity Index scores (p=0.005), transplant recipient status (p< 0.001) and duration of illness less than 7 days (p=0.005). Importantly, patients with high genomic load were more likely to reach the primary endpoint (p=0.001), and had higher PSI scores on admission (p=0.03). In multivariate analysis, high genomic load remained an independent predictor of primary outcome. Results remained significant in sensitivity analyses. Flow Chart Prediction of Outcomes Based on Genomic Load Prediction of Outcomes Based on Genomic Load and Pneumonia Severity Index Conclusion: High genomic load of SARS-CoV-2 in nasopharyngeal samples at the time of admission is independently associated with mortality and intubation. This finding should prompt further research on the role of viral load as a clinical predictor and possible modifiable risk factor for adverse outcomes as treatment strategies evolve in this global pandemic. Disclosures: All Authors : No reported disclosures